To Be and Not to Be: Hamlet’s Identity. Lacan’s Errors and His Disappointing Interpretation of Shakespeare (ENTHYMEMA, 2019)
Hamlet’s desire must be examined in relation to the desire to be, that is the desire for identity: this is the claim upheld in this study. Consequently, the article begins by making a distinction between the desire to be and the desire to have: this distinction was expressed in a new way by Freud, but was never adequately developed either by Freud himself or by Lacan. Therefore, the desire to be has remained prisoner of the Oedipus complex, even in Lacan’s reformulation in which it basically proves to be the desire to be the Phallus.Yet the desire to be must be understood starting from the “modal revolution” introduced by Heidegger, and this allows us to appreciate the more innovative thesis in Freud’s essay, “Group Psychology and the Analysis of the Ego” (1921). Identity is a relationship that may be considered to be a coincidence or a non-coincidence with oneself: in the latter case, we will refer to an “overcoming identity.” As a result, philosophy, the theory of the subject and the theory of literature are called upon to investigate the modes of identity.From the perspective of the modes of being, Hamlet is analyzed here starting from his refusal to subordinate his own identity to the role of avenger. His desire oversteps the borders of neurosis and melancholy, in which it had traditionally been imprisoned (also by Lacan). Hamlet is a hero of non-coincidence: he goes beyond the models that appear to him to be inadequate and attempts to construct a flexible identity. Adopting the mask of madness, he has the opportunity to display his linguistic creativity. This does not deny that Hamlet is a tormented hero: the shadow of his father and the lust of his mother are obstacles to the desire for identity.This interpretation is only delineated in the last pages of the article. It is first necessary to show that the limitations of Lacan’s interpretation derive from a narrow conception of the Symbolic and the desire to be for which Lacan never acknowledges creative possibilities. The Lacanian notion of “lack” is a logical and epistemological obstacle that prevents the development of the logic of flexibility and the nonof “non-coincidence.”